Change Management for Improving the Quality of Public Services - Krasnykov, Yevgen (Theory and Practice of Public Administration, 2023)
The article describes peculiarities of introduction of changes in organizational structures to improve the quality of public services and resistance to these changes as an inevitable process. It is proved that the professional activity of a manager in the public sector depends on change management, and resistance to them is the main element of the change management system. The essence and interconnection of the concepts of “change management” and “resistance to change” are substantiated. The author considers the main theories of change that are used in practice in the public sector: energy, mathematical, economic, biological, systemic, psychological, psychoanalytic, political, sociological, cultural and developmental. It is proved that most theories of change emphasize that resistance to these changes is inevitable. The main reasons, forms and types of resistance in the implementation of changes and innovations by the head of a public organization are formulated.People’s ability to adapt and deal with external variability are two key variables in determining how they will respond to change. It is taken into account that external variability is usually high for most organizations providing public services. But at the same time, public authorities, especially during the war in Ukraine, are mainly staffed by people who prefer a stable environment and well-structured ways of activity. This means that managers can expect significant resistance when trying to implement changes in public services, despite the goals of these changes.The author formulated possible fluctuations in the attitude to changes in personnel from the announcement of them to their implementation. It is confirmed that the main reasons for resistance to changes in the provision of public services aimed at improving these services include: adherence to bureaucratic habits related to delegation of authority; skepticism; challenges associated with many hierarchical levels of authority, accountability and reporting; the tendency to push decision-making upwards, which is contrary to approaches aimed at increasing self-control and independence; relationships that are governed by the interests of many stakeholders; the presence of conflicting interests and values, and others. It is noted that the main forms of resistance to change include: apathy, tardiness, sabotage, going to the hospital, absenteism, procrastination, working by the rules, slow work, leaks in the media, backstage criticism and others. The categories of employees in the sphere of public provision, which are most vulnerable to any changes, are defined.The author of the article developed recommendations for overcoming resistance to changes and their effective implementation to improve the quality of public services.